BILANGAN INVERS DOMINASI TOTAL PADA GRAF BUNGA DAN GRAF TRAMPOLIN - Febby Desy Lia; Nilamsari Kusumastuti; Fransiskus Fran (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2022)
Given a simple, finite, undirected and contains no isolated vertices graph , with  is the set of vertices in  and  is the set of edges in . The set  is called the dominating set in  if for every vertex of  is adjacent to at least one vertex in . The set  is called the total dominating set in graph  if for every vertex in  is adjacent to at least one vertices in . If  is the total domination set with minimum cardinality of the graph  and  contains another total domination set, for example , then  is called the inverse set of total domination respect to . The minimum cardinality of an inverse set of total domination is called the inverse of total domination number which is denoted by .The set of domination and total domination is not singular. A graph that has a total domination set does not necessarily have a inverse total domination set. In this study, exact values are found of , and  and,, n is even and , where be a flower graph and T<span style='font-size:10.0pt;mso-ansi-font-siz